Of Recognition In Asean Free Trade - Siti Nurahmi Nasution siti; Adwani Adwani (Al-Makki Publisher, 2023)
The purpose of this paper is to analyze the implementation of the ASEAN Free Trade Agreement and to analyze the principle of recognition in ASEAN free trade. The research method in this paper is using normative legal research methods. This research is a study that uses secondary materials as the main reference material in research. Secondary materials are library materials in the form of documents and scientific papers as sources. The documents used are in the form of legal materials such as laws and regulations, agreements, legal theories, and potential scientific papers as reference material for writing. This research is a normative research on the principle of recognition in ASEAN free trade which will be described analytically the entire object systematically according to the data obtained.